Association between access to water, sanitation, and hygiene (WASH) practices and stunting among children under five: A systematic review and meta-analysis - Nisa, Ananda Fadila; Pratiwi, Cesa Septiana; Warsiti (Journal of Evidence-based Nursing and Public Health, 2026)
Background: Stunting is a chronic malnutrition condition that leads to impaired growth and development, primarily caused by inadequate water, sanitation, and hygiene (WASH) conditions. This study aims to systematically review and meta-analyze the association between WASH factors and stunting in children under five. Methods: This meta-analysis was conducted using the PICO research question. The study population involves children aged 0 to 59 months to analyze how unimproved water, sanitation, and hygiene compare with improved practices in affecting stunting outcomes. Relevant articles were systematically retrieved from several databases including PubMed, BMC, ScienceDirect, and Springer Link, with inclusion criteria focusing on cross-sectional and longitudinal studies published between 2020 and 2025. All gathered data were subsequently synthesized and analyzed using the Review Manager 5.4 application to ensure a rigorous evaluation of the research findings. Findings: Meta-analysis included 6 studies from Indonesia and Ethiopia. The risk of stunting increased with unimproved sanitation (aOR = 1.33; 95% CI = 1.20–1.48; p < 0.00001), unimproved hygiene (aOR = 1.16; 95% CI = 0.73–1.84; p = 0.530) unimproved water (aOR = 1.10; 95% CI = 0.94–1.29; p = 0.250) increased the risk of stunting, but it was statistically not significant. Conclusion: Unimproved water, sanitation and hygiene increase the risk of stunting. Novelty/Originality of this article: This study provides a separated evaluation of water, sanitation, and hygiene factors using evidence from 2020–2025 to clarify specific WASH-related determinants contributing to stunting among children under five.